Kesehatan Keuangan Keluarga melalui Literasi Keuangan Guna Mewujudkan Kesejahteraan Keluarga pada PKK Desa Ngaresrejo Sidoarjo: Family Financial Health through Financial Literacy to Achieve Family Welfare at the Family Welfare Movement (PKK) in Ngaresrejo Village, Sidoarjo - Utami Puji Lestari; Yayu Sriwahyuni Hamzah; Febriarsita Eka Sasmita (Jurnal Pelayanan dan Pengabdian Masyarakat Indonesia, 2026)
: Family well being is strongly influenced by the ability to manage finances wisely and systematically. However, low levels of financial literacy among communities often lead to issues such as imbalance between income and expenditure and lack of proper financial planning. This community service program aimed to improve the understanding and skills of PKK women in Ngaresrejo Village, Sidoarjo, in managing household finances. The method used was a participatory approach consisting of socialization, educational sessions, group discussions, and hands-on assistance in simple financial record-keeping. A total of 25 participants were actively involved in all stages of the program. Evaluation was conducted using pre-test and post-test assessments, as well as participant feedback on the implementation process. The results showed an increase in participants’ understanding from 39% in the pre-test to 61% in the post-test. In addition, 63% of participants expressed satisfaction with the program, indicating that the activity was relevant and beneficial. Qualitatively, the program also encouraged positive behavioral changes in financial management, such as recording income and expenses, prioritizing needs, and improving saving habits. Furthermore, the emergence of active participants as local leaders indicates the potential sustainability of the program within the community. In conclusion, this community service program effectively enhances family financial literacy and contributes to improving community well-being in a sustainable manner.